Peran Strategis Bank Syariah dalam Mendorong Keuangan Hijau dan Ekonomi Berkelanjutan - Ningsih, Anggun Wahyuni (Maliki Interdisciplinary Journal, 2025)
This research discusses the strategic role of Islamic banks in supporting green finance and sustainable economy in Indonesia. With the increasing issue of climate change and environmental degradation, Islamic banks are expected to contribute through ethical and environmentally friendly financial principles. This research uses a qualitative method with a literature study approach to analyze the impact of green financing by Islamic banks on a sustainable economy. The results show that Islamic banks play an important role in supporting environmentally friendly projects through sharia-based financial products such as Green Murabahah, Green Ijarah, and Green Sukuk. By integrating sharia principles that focus on sustainability, Islamic banks finance renewable energy projects, green infrastructure, as well as environmentally friendly waste management. Islamic banks not only fulfill economic goals but also contribute to social and environmental welfare. The impact of green financing by Islamic banks includes the creation of new jobs in the renewable energy and environmental management sectors, reduction of carbon emissions, and improved energy efficiency. In addition to achieving economic goals, green financing also contributes to social welfare and environmental preservation.